Identifikasi Potensi dan Strategi Pengelolaan Kawasan Pesisir Pantai Bintalahe | Identification of the potential and strategies for management of the Bintalahe Coast - Sri Dewi Yulianti Gawa; Femy M Sahami; Citra Panigoro (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2017)
Penilitian ini bertujuan untuk mengetahui identifikasi potensi sumberdaya alam dan sumberdaya manusia dengan strategi pengelolaan pengembangan kawasan wisata pesisir pantai Bintalahe. Penelitian ini dilaksanakan selama 3 bulan, yaitu Bulan Mei – Juli 2017 Metode yang digunakan dalam pengumpulan data adalah metode observasi dan metode wawancara. Analisis data menggunakan analisi SWOT. Potensi sumberdaya alam yang dimiliki oleh pesisir Pantai Bintalahe terdiri dari sumberdaya pantai dan sumberdaya perikanan. Hasil analisis SWOT menunjukkan bahwa strategi yang penting dalam pengembangan kawasan wisata pesisir Bintalahe adalah partisispasi masyarakat dan pengunjung dalam aktivitas ekowisata pantai dan pengelolaan lingkungan pesisir. This research aims to find out the identification of the potential of natural resources and human resources with the management strategy of developing the Bintalahe coastal tourism area. This research was conducted for 3 months, namely May - July 2017 The method used in data collection is the method of observation and interview methods. Data analysis using SWOT analysis. The potential of natural resources owned by the coast of Bintalahe consists of coastal resources and fisheries resources. The results of the SWOT analysis show that an important strategy in developing the Bintalahe coastal tourism area is the participation of the community and visitors in coastal ecotourism activities and the management of the coastal environment. Katakunci: Potensi; strategi; pengelolaan; pesisir. Keywords: Potential; strategy; management; the coast